The methodology of defect thermal characterization in pulsed thermal NDT based on 3D numerical solutions and polynomial approximation - Vavilov V. P. Vladimir Platonovich; Chulkov A. O. Arseniy Olegovich; Ganina O. A. Olesya Alekseevna; Kuimova M. V. Marina Valerievna; Makushev O. A. Oleg Alekseevich (2026, 2026)
Title screen